The Rise of Interactive Governance and Quasi-Markets - Denters, Bas (Springer Netherlands, 2003)
This volume fills this gap and presents case studies - particularly in consensus democracies such as the Netherlands, Flanders, and Germany but also in majoritarian democracies such as the UK and Canada - that describe and analyze the impact of the changing role of government, and focus on the introduction of interactive governance and the introduction of quasi-markets. The chapters explore how new forms of governance combine with the traditional institutions and processes of public decision making
Lizenzpflichtig